Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1592/phco.26.12.1703
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy Considerations in Advanced Cardiac Life Support

Abstract: Cardiac arrest and sudden cardiac death remain major causes of mortality. Early intervention has been facilitated by emergency medical response systems and the development of training programs in basic life support and advanced cardiac life support (ACLS). Despite the implementation of these programs, the likelihood of a meaningful outcome in many life-threatening situations remains poor. Pharmacotherapy plays a role in the management of patients with cardiac arrest, with new guidelines for ACLS available in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 197 publications
0
12
0
1
Order By: Relevance
“…Epinephrine and vasopressin are effective drugs for cardiac arrest, as they can stimulate ROSC (9 -11). Epinephrine can facilitate defibrillation, induce positive hemodynamic effects, and increase both systemic pressure and myocardial perfusion (12,13). This study demonstrated the efficacy of epinephrine administration in obtaining PROSC.…”
Section: Discussionmentioning
confidence: 52%
“…Epinephrine and vasopressin are effective drugs for cardiac arrest, as they can stimulate ROSC (9 -11). Epinephrine can facilitate defibrillation, induce positive hemodynamic effects, and increase both systemic pressure and myocardial perfusion (12,13). This study demonstrated the efficacy of epinephrine administration in obtaining PROSC.…”
Section: Discussionmentioning
confidence: 52%
“…Details of these cases are urgently needed to generate improved rescue protocols. It is possible that the presumed anaphylactic reactions were in fact hypotensive reactions, and would have benefitted from treatment with volume administration instead of anaphylactic reaction treatment with vasopressor infusion (38). Guidelines for the treatment of iron infusion related reactions specifically recommend fluids ahead of anaphylaxis therapy (34).…”
Section: Discussionmentioning
confidence: 99%
“…Routine use of sodium bicarbonate in cardiac arrest is controversial because of a lack of outcome studies and proven benefit. 3,15 Limitations There are limitations associated with this study. This was a single-center analysis with a limited number of participants and was underpowered to detect a difference in the primary outcome.…”
Section: Discussionmentioning
confidence: 98%